2019
DOI: 10.1177/1088357619881221
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Postsecondary Expectations Among Parents of Youth With Autism Spectrum Disorder

Abstract: Research suggests higher parent expectations can predict more independent outcomes of youth with autism spectrum disorder (ASD), yet little is known about how parents’ expectations are formed. To gain an understanding of their formation, we conducted semi-structured interviews with seven parents of adolescents with ASD. Three main types of influences on parent expectations were identified: factors related to the youth, to the parent, and to social and societal forces external to the family. Although not direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…43 In the interviews, parents who disagreed with their child's visions of the future often presented concerns and doubts about their ability to achieve those visions. 32,43 These findings are consistent with research indicating that parents of autistic adolescents perceive greater problems than their child perceives, such as in the areas of anxiety and social functioning. 3,[44][45][46] Although our results may not be surprising, they are concerning given research that suggests a relationship between parent expectations and employment for youth with disabilities, including autistic youth.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…43 In the interviews, parents who disagreed with their child's visions of the future often presented concerns and doubts about their ability to achieve those visions. 32,43 These findings are consistent with research indicating that parents of autistic adolescents perceive greater problems than their child perceives, such as in the areas of anxiety and social functioning. 3,[44][45][46] Although our results may not be surprising, they are concerning given research that suggests a relationship between parent expectations and employment for youth with disabilities, including autistic youth.…”
Section: Discussionsupporting
confidence: 83%
“…Future research should attend to parent factors since prior studies suggest that parent psychological factors (e.g., beliefs, depression, anxiety) relate to parent expectations. 32,49 Further, although we could not examine the linkage between adolescent or parent visions of the future and their longitudinal postsecondary outcomes in the current study, we know from prior research among youth with disabilities that both can be significant predictors of outcomes. 24 This study contributes to a growing body of literature emphasizing the importance of including the perspectives of autistic adolescents in research and for them to have an active and substantial role in their own transition planning, rather than focusing only on the perspectives of parents.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The pre–post measures we used demonstrated acceptable internal consistency with a national sample of 269 parents of autistic youth without ID in prior work ( Kirby, Feldman, et al, 2020 ); α coefficients from that study are reported in the following paragraphs. Before T1, a nonrandom subsample of 10 parent participants (i.e., those who signed up early enough and were willing) completed study measures over a 6-wk nonintervention period, demonstrating no significant changes ( p ≥.10) on any of the measures.…”
Section: Methodsmentioning
confidence: 95%
“…Parents of autistic youth must often make critical decisions about postsecondary activities (e.g., the types of supports their child needs, whether their child will seek higher education or employment opportunities) during or, ideally, before this transition period ( Lounds et al, 2007 ). Parents of autistic youth also report considerable uncertainty when it comes to their child’s future ( Kirby, Bagatell, & Baranek, 2020 ), which can have the unintentional result of limiting opportunities for the child ( Cheak-Zamora et al, 2017 ). Limited opportunities for decision making and skill development can restrict self-determination, which has been well established as a critical aspect of the transition to adulthood for youth with disabilities ( Paradiz et al, 2018 ).…”
Section: Need For Parent-based Interventionmentioning
confidence: 99%